(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The floods of the area of ​​the western basin are considered the most dangerous in the study area, and that is due to the nature of the water drainage network of the area and Qasioun landfill in the basin. Together, they comprise (84.2%) of the study area, compared to (15.8%) for human use. It stands in contract to the eastern slope where (41.4%) is the natural area and (58.6%) is for the human use. The following factors are the main reasons behind the flood disaster in (26/4/2018): The main characteristic of the urban use is random housing due to the high rate (69.8%) of irregularly multi-story buildings. Another characteristic is the overlap between the main roads, the valleys and the drainage network without any modification; the roads followed the original shape of the valleys, which increased the hazard wof the floods passing through them. The affected buildings were identified according to the field survey of the residential buildings and were classified into three categories: Highly vulnerable to flood hazards buildings, hich are located on both sides of the roads that are complementary to the end of the mountain drainage networks and the cement trenches. The general proportion of this category of buildings is (14.9%). The second category is the Less vulnerable to flood hazards buildings, which are located on both sides of second level roads, and they make (36.9%) of the buildings. The last category is Safe buildings, which are located far from direct contact with flood waters and make (48.2%) of the total buildings in the region. The effects of floods in the study area varied, and were divided into health, economic and social effects. Finally, three recommendations were suggested to reduce the risk of the floods: avoidance, prevention and mitigatio